Chapter Il puzzle dei licenziamenti ed il bilanciamento dei valori tra tecniche di controllo e strumenti di tutela - ZOLI, CARLO (Studi e saggi, 2022)
This paper deals with the issue of dismissals, focusing both on the control techniques regarding the power to dismiss, as well as on forms of workers' protection. It reconstructs the evolution of the more recent legislative reforms, examining how they have balanced the founding values of the Italian legal system. In this context, sentence n. 194/2018 of the Consitutional Court takes on fundamental importance. It provides essential systematic principles and guidelines, which both the Legislator and judges can refer to, even when there are complex problems of interpretation and unconstitutional aspects. Consequently, once again, the Legislator may need to intervene.